The One Third Bequest Limit to Mosques and Heir Protection - Afra Nafisah; Wiwie Sapitri (IAIN Parepare, 2026)
This study examines the one third bequest limit to mosques and the protection of heirs in Decision Number 329/Pdt.G/2020/PA.Batg. The issue arises from a dispute over a monetary bequest to Masjid Nurul Ikhlas, where the testator’s religious intention conflicted with the heirs’ inheritance rights. Previous studies have mainly discussed obligatory bequests and the position of dzawil arham heirs, while judicial reasoning on bequests to religious institutions and the one third limit remains underexplored. This study aims to analyze the legal status of a bequest to a mosque, the judge’s reasoning in determining its validity and enforceability, and its implications for heir protection. This research uses a normative juridical method with case, conceptual, and statutory approaches. The findings show that a bequest to a mosque is legally permissible under Islamic inheritance law as long as it meets formal and material requirements and does not exceed one third of the estate without the heirs’ consent. In the case analyzed, the court declared the Rp200,000,000 bequest valid because it was supported by written evidence, notarial legalization, and witness testimony. However, its execution was limited to Rp117,000,000 as one third of the proven estate. This study recommends clearer evidentiary and estate valuation standards in bequest disputes involving religious institutions.